Analysis of the Content of Suspended Solids and Sedimentary Organic Matter in the Coastal Waters of Bokor, Meranti Island Regency - Saputra, Hafiz Zikra; Nurrachmi, Irvina; Yoswaty, Dessy (Journal of Coastal and Ocean Sciences, 2026)
This study aims to analyse the concentrations of Total Suspended Solids (TSS) and sediment organic matter, as well as their relationship, in the coastal waters of Bokor Village, Kepulauan Meranti Regency. The research was conducted from December 2024 to January 2025 using a survey method at three observation stations selected based on varying levels of human activity. TSS analysis was performed gravimetrically according to the Indonesian National Standard (SNI 6989.3:2019), while sediment organic matter was analysed using the Loss on Ignition (LOI) method. The results showed that TSS concentrations ranged from 10.4 to 17.56 mg/L and were within the good-quality standard for marine waters. The concentration of sediment organic matter ranged from 3.0% to 5.7%, which is categorised as low. A simple linear regression analysis indicated a weak positive correlation between TSS and sediment organic matter. This suggests that suspended solids account for only 10.1% of the variability in sediment organic matter, with the remaining variation influenced by other environmental factors.